2014
DOI: 10.4028/www.scientific.net/amr.939.655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of TiO<sub>2</sub> Nanotubes Formation on the Surface of Pure Ti and Ti-6Al-4V Alloy

Abstract: The present paper deals with the investigation of the mechanisms of TiO2 nanotubes formation on titanium surfaces during anodization process. The samples were made of pure Ti Grade-2 and Ti-6Al-4V alloy. They were grinded, etched with 0,5 wt. % HF acid and anodized. The anodization was done in electrolyte containing 0,5 wt. % HF acid using DC power supply with graphite electrode as cathode. The samples were investigated by SEM, EDAX and XRD analysis. The results show two different mechanisms of formation of Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…e data presented above were proportional to the previously reported studies [48,69,80]. e nanotube dimensions, morphology, and EDS analysis of the anodised Ti-6Al-4V titanium alloy specimens showed a similar trend to those reported in previous publications [79,[89][90][91][92]. e EDS analysis revealed that the anodic layer was composed of titanium, aluminium, vanadium, oxygen, and traces of carbon and fluorine.…”
Section: Upscaling and Optimisationsupporting
confidence: 85%
See 1 more Smart Citation
“…e data presented above were proportional to the previously reported studies [48,69,80]. e nanotube dimensions, morphology, and EDS analysis of the anodised Ti-6Al-4V titanium alloy specimens showed a similar trend to those reported in previous publications [79,[89][90][91][92]. e EDS analysis revealed that the anodic layer was composed of titanium, aluminium, vanadium, oxygen, and traces of carbon and fluorine.…”
Section: Upscaling and Optimisationsupporting
confidence: 85%
“…It could be due to the different electrolyte and base material composition used, as well as the effect of the additional pickling process before the anodisation is carried out to remove the naturally occurred oxide layer. ese phenomena have been previously demonstrated in other comparable studies [90,93,94]. In addition to that, the literature has also shown that changes in nanotube length are the least significant for the modulation of cellular behaviour [50], unlike the pore size and interpore distance, which are important.…”
Section: Upscaling and Optimisationsupporting
confidence: 57%
“…One of the pioneering efforts to utilize electrochemical anodization as an innovative approach for the surface modification of Ti-based alloys was performed by Dunn et al [ 221 , 222 ], where porous surface coatings are formed by anodization and incorporating antibiotics onto the oxide surface. Zwilling et al [ 223 ] also reported that anodization on Ti and Ti–6Al–4V alloys in the F − ion solution is an effective approach to attain tunable tubular oxide layers under different anodization conditions [ 16 , 17 , 65 , 133 , [224] , [225] , [226] , [227] , [228] , [229] , [230] , [231] , [232] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] , [241] , [242] , [243] , [244] , [245] , [246] , [247] , [248] , [249] , [250] , [251] , [252] , [253] , [254] , [255] , [256] , [257] , [258] , [259] , [260] , [261] , [262] ]. Since the Ti–6Al–4V alloy is a dual-phase alloy, the development kinetics of nanotubes are dissimilar for the α and β phases [ 69 ].…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…The anodisation started with randomly arranged porous structures and ended with uniformly arranged nanotubes. Meanwhile, Dikova and colleagues defined the mechanism behind the growth of nanotube on the surface of Ti-6Al-4V with the surface of their samples being coated up to 80% with nanotubes in 7 hours [26]. During the process, where they used just hydrofluoric acid (HF), the synthesis of the nanotubes started with the presence of nano-seeds.…”
Section: Stages Of Nanotube Formationmentioning
confidence: 99%
“…The process as to why the nanotubes are uniformly arranged had been described by different groups [26] [27]. The group of Dikova performed a step by step analysis of the nanotube formation in hydrofluoric acid at 25 V and provided microscopic images of the different structures at different intervals.…”
Section: Introductionmentioning
confidence: 99%